The Role of Explicit Teaching Remedy in Enhancing Grammatical and Lexical Cohesive Devices Problem in Second Year Students Writing’ s at the University of Constantine 01 - Abid, Meriem (Journal of Human Sciences, 2017)
Cohesion is the use of grammatical and lexical cohesive devices to tie ideas across texts; it is also an important element for maintaining coherence in any piece of discourse. Researchers agreed that this problematic area to EFL learners; however, no curative medicine has been given yet. Therefore, this study focuses on the explicit teaching approach with the purpose of teaching different grammatical and lexical ties to second year students of English at the University of Constantine 1. An experimental design is used to test the efficacy of this approach where two experimental (EXP) and control (CTR) groups undertook the tests. After the analysis of both the pre- and post- tests scores, the results revealed that the explicit teaching is successful in solving cohesive devices problem simply because the improvements in the EXP group is far higher than those of the CTR group, though there are some aspects such as: ellipsis and substitution which have not enhanced significantly.